2018
DOI: 10.1080/07315724.2017.1410867
|View full text |Cite
|
Sign up to set email alerts
|

Functional Food and Cardiovascular Disease Prevention and Treatment: A Review

Abstract: Cardiovascular disease (CVD) is now the leading cause of death globally and is a growing health concern. Lifestyle factors, including nutrition, play an important role in the etiology and treatment of CVD. Functional foods based on their basic nutritional functions can decrease the risk of many chronic diseases and have some physiological benefits. They contain physiologically active components either from plant or animal sources, marketed with the claim of their ability to reduce heart disease risk, focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
69
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 270 publications
0
69
0
4
Order By: Relevance
“…11 Among potential cardioprotective effects of polyphenols, the following are postulated most frequently: inhibition of low -density lipoprotein oxidation, antioxidant action, improvement of endothelial function, and reduction of platelet aggregation. 12 Besides, antiplatelet and anti -inflammatory activity of plant polyphenols is well documented. 13,14 Numerous publications have reported that plant polyphenols reduce the CRP level in inflammatory diseases.…”
mentioning
confidence: 99%
“…11 Among potential cardioprotective effects of polyphenols, the following are postulated most frequently: inhibition of low -density lipoprotein oxidation, antioxidant action, improvement of endothelial function, and reduction of platelet aggregation. 12 Besides, antiplatelet and anti -inflammatory activity of plant polyphenols is well documented. 13,14 Numerous publications have reported that plant polyphenols reduce the CRP level in inflammatory diseases.…”
mentioning
confidence: 99%
“…Typical functional food contains bioactive compounds including dietary fiber, polyunsaturated fatty acids, phytochemicals and antioxidants that have potential roles in reducing the risk of chronic diseases (Gazem and Chandrashekariah, 2016). Chia seed is among the growing functional food that have been reported to protect the cardiovascular system, exhibit anti-inflammatory properties, anti-oxidative properties and control blood sugar and lipid metabolism (Gazem and Chandrashekariah, 2016;Marcinek and Krejpcio, 2017;Asgary et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that whole grains may play a central role in the prevention of chronic diseases (Vuksan et al, 2007). Epidemiological studies suggest a strong association between increased consumption of whole-grain foods and reduced risk of diabetes and cardiovascular disease (Ho et al, 2013;Alissa and Ferns, 2014;Asgary et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate types of diets and levels of physical activities are believed to be major determinants of maintaining optimal health [1,2]. Many studies have reported that regular consumption of certain 2 of 13 foods, particularly plant-based foods, such as whole grains, fruits, and vegetables, as well as fish, are associated with decreased prevalence of chronic diseases, specifically cardiovascular disease [3,4]. Phytochemicals that are contained within these foods are believed to mediate these health benefits and include phytosterols, dietary fiber, dietary antioxidants, oleic acid, and docosahexaenoic acid (DHA).…”
Section: Introductionmentioning
confidence: 99%